Rainfall and atmospheric circulation simulated by the WRF regional model in Southern Africa: sensitivity to the physics and internal variability - (:unkn) unknown (My University, 2011)
This study evaluates the capability of the regional climate model WRF to simulate Southern African rainfall and associated atmospheric circulation, particularly over South Africa, a country covered by a dense network of in situ observations. Three sets of simulations are performed at a 35km horizontal resolution during the core of the austral rainy season (December to February: DJF) with 6-hourly forcings provided by ERA40 reanalysis. The first set quantifies sensitivity of the simulated climate to the parameterizations of atmospheric convection, planetary boundary layer and microphysics. The retained case study (DJF 1993-1994: DJF94) is representative of the South African rainfall climatology. Seasonal rainfall patterns, their intensities and their intraseasonal characteristics are primarily controlled by convective schemes. Seasonal biases vary by 100% according to the three tested schemes (Kain-Fritsch, Betts-Miller-Janjic and Grell-Dévényi). Planetary boundary layer and microphysics schemes produce lesser uncertainties, but they can cumulate their effects with convection schemes. The second set evaluates the seasonal mean state and the recurrent daily rainfall patterns for the 1971-1999 period using one satisfactory configuration determined for DJF94. WRF clearly improves the South African rainfall climatology upon ERA40, in particular due to a stronger depression over Angola. Except for weak rainy days, WRF simulates accurately the main observed rainfall patterns at the daily timescale, despite frequent shifts of a few days. The third set quantifies internal variability through two 30-member ensemble simulations. Internal variability is modulated by the parameterization of atmospheric convection (stronger in Kain-Fritsch compared to Grell- Dévényi). In both cases, the geography of the internal variability at daily timescale is very close, with maximum located along a large band oriented north-west to south-east. Uncertainties concern the morph
Keywords: African Research